BATAS 2 LAUTAN DALAM PERSPEKTIF TAFSIR ILMI: STUDI KOMPARATIF BUKU "BATAS DUA LAUT" KARYA AGUS S. DJAMIL DAN "SAMUDRA" KARYA KEMENAG RI - Melisa Haryati; Khairul Kahfi; Fahrul Ihsan; Andi Rosa (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2026)
A comparative study between Agus S. Djamil's book 'Batas Dua Laut' (The Border of Two Seas) and the Ministry of Religious Affairs of the Republic of Indonesia’s (Kemenag RI) book 'Samudra' (The Ocean) examines the interpretation of verses regarding marajal bahrain (the meeting of two seas). Utilizing a qualitative method with a descriptive-comparative approach and epistemological discourse analysis, this study investigates the differences in substance, methodology, and argumentative strength between the two works. The results indicate that Kemenag RI employs ijtihad jam'i (collective reasoning), which focuses on scientific evidence of Allah's omnipotence. Their research demonstrates micro-scale physical oceanographic phenomena, such as haloclines, thermoclines, and fronts in bodies of water like the Strait of Gibraltar. Conversely, Agus S. Djamil provides an interpretation that transcends the boundaries of physical oceanography, encompassing macro-geographical and geo-economic aspects. He defines the 'border of two seas' as the location of the Indonesian archipelago between the Pacific and Indian Oceans, and 'lu'lu wal marjan' (pearls and corals) as strategic resource potentials, such as oil and gas reserves on shelf margins and upwelling zones. Critical analysis reveals that Kemenag RI’s book excels in shar'i authority and epistemological caution (zero-hallucination), whereas Djamil’s book stands out for its pragmatic contextualization and its impetus for a maritime economic revival, despite some conclusions being highly speculative. The tafsir ilmi (scientific exegesis) from both works is vital for resolving the debate between science and religion, demonstrating that the Qur'an subtly revealed the complexities of the ocean long before the era of contemporary marine exploration.